1995
DOI: 10.1128/aem.61.5.1720-1726.1995
|View full text |Cite
|
Sign up to set email alerts
|

Chitinolytic Enterobacter agglomerans Antagonistic to Fungal Plant Pathogens

Abstract: Three Enterobacter agglomerans strains which produce and excrete proteins with chitinolytic activity were found while screening soil-borne bacteria antagonistic to fungal plant pathogens. The chitinolytic activity was induced when the strains were grown in the presence of colloidal chitin as the sole carbon source. It was quantitated by using assays with chromogenic p-nitrophenyl analogs of disaccharide, trisaccharide, and tetrasaccharide derivatives of N-acetylglucosamine. A set of three fluorescent substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
0
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(131 citation statements)
references
References 35 publications
6
118
0
7
Order By: Relevance
“…For neither protein was a clear N-terminal signal peptide predicted, suggesting they are cytoplasmic proteins. Overexpressed and purified HexI showed activity towards all three tested chitin analogs (Table 2), which is consistent with previous reports on N-acetylglucosaminidases (Chernin et al, 1995). We were not able to StrepTag-purify HexII from overexpressing E. coli cells (Table 2).…”
Section: Resultssupporting
confidence: 89%
“…For neither protein was a clear N-terminal signal peptide predicted, suggesting they are cytoplasmic proteins. Overexpressed and purified HexI showed activity towards all three tested chitin analogs (Table 2), which is consistent with previous reports on N-acetylglucosaminidases (Chernin et al, 1995). We were not able to StrepTag-purify HexII from overexpressing E. coli cells (Table 2).…”
Section: Resultssupporting
confidence: 89%
“…These results indicated that expression of Chi92 on the cell surface enhanced the ability for inhibition of fungal growth in vitro. It was reported that the chitinase-producing bacteria, including Aeromonas caviae (Inbar & Chet, 1991), Enterobacter agglumerans (Chernin et al, 1995), and Serratia marcescens (Ordentlich et al, 1988), are potential biocontrol agents against phytopathogenic fungi. The chiA gene from S. marcescens has been expressed in E. coli, and the chitinase was shown to be effective in the reduction of disease incidence caused by S. rolfsii and R. solani (Shapira et al, 1989).…”
Section: Antifungal Activitiesmentioning
confidence: 99%
“…In controlling fungal plant pathogens, a variety of mechanisms contribute to the biocontrol activity of microbes. Cell-wall-degrading enzymes (CWDEs), such as b-1,3-glucanases, cellulases, proteases, and chitinases, are involved in the antagonistic activity of some biological control agents against phytopathogenic fungi [12][13][14][15][16]. In particular, numerous correlations between fungal antagonism and bacterial production of chitinases and/or b-1,3-glucanases have been noted [17].…”
Section: Introductionmentioning
confidence: 99%